Resurrected to Eternal Life : On Dying and Rising - Moltmann, Jürgen (Book collections on Project MUSE., 2021)
In this daring meditation, Jürgen Moltmann interrogates dying, the nature of death, and the hope of eternal life. For Moltmann, the living soul that awakens to eternal life is not a ghost in a machine, but the Lebensgestalt, the shape and story of a life. Seasoned readers will find here a capstone to Moltmann's career of theological exploration, while those new to his thought will find a concise and elegant entry point into his work.